2004
DOI: 10.1177/1531244504422003
|View full text |Cite
|
Sign up to set email alerts
|

In the Best Interests of Children: A Proposal to Transform the Adversarial System

Abstract: In the traditional family law and child protection litigation where the court is asked to make determinations based on the best interests of aminor, the adversarial, rights-based model often fails to serve the interests of children and families and may be more harmful than beneficial to children relative to other possible methods of dispute resolution. This article examines the shortcomings of such an adversarial, rights-based model; briefly highlights the literature on dispute resolution systems design; and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…This expensive "merry-go-round" clogs the system, but its greatest impact is on children who are caught in the middle of a grueling siege that can often last for decades. Firestone and Weinstein (2004) observed that the legal system by its very adversarial nature is ill suited to deal with most post-divorce problems, in which "family relationships have become legalized in such a way that the system loses sight of the human problems in context and focuses only on addressing answers to legal questions" (p. 203).…”
Section: The Parenting Coordinator Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…This expensive "merry-go-round" clogs the system, but its greatest impact is on children who are caught in the middle of a grueling siege that can often last for decades. Firestone and Weinstein (2004) observed that the legal system by its very adversarial nature is ill suited to deal with most post-divorce problems, in which "family relationships have become legalized in such a way that the system loses sight of the human problems in context and focuses only on addressing answers to legal questions" (p. 203).…”
Section: The Parenting Coordinator Modelmentioning
confidence: 97%
“…Firestone and Weinstein (2004) succinctly observed that the current domestic law system, with its emphasis on adversarial posturing and legal rights of the parents, is not the appropriate forum to resolve the problems of divorcing or divorced families.…”
Section: The Parenting Coordinator Modelmentioning
confidence: 97%
“…Child development and family dynamics are a delicate matter, and the discretionary power of judges an area in which they are neither professionally trained, nor competent to assess third party evaluations or professional literature on the matter, is a recipe for disaster. In making decisions regarding child custody and access, judges do not consult relevant research on child outcomes (Kelly and Lamb, 2000), and are highly susceptible to error bias (Firestone and Weinstein, 2004;McMurray and Blackmore, 1992): judges are not infallible and routinely make mistakes, awarding custody to the more litigious parent, with children running the risk of being placed in the exclusive care of an abusive parent. Melton (1989) presents a startling account of how little social science knowledge trickles down into legal policies that are intended to benefit children in the child custody realm.…”
Section: Equal Parenting Provides a Clear And Consistent Guideline Fomentioning
confidence: 98%
“…Cases are largely decided by the way evidence is presented in court, and thus the BIOC is subject to judicial error (Firestone and Weinstein, 2004). The BIOC standard also makes the court largely dependent on professional custody evaluators.…”
Section: The Best Interests Of the Child Standardmentioning
confidence: 99%